Early Chinese texts on painting - Bush, Susan; Shih, Hsio-yen, 1933- (Hong Kong University Press, 2012)
"For students of Chinese art and culture this anthology has proven invaluable since its initial publication in 1985. It collects important Chinese writings about painting, from the earliest examples through the fourteenth century, allowing readers to see how the art of this rich era was seen and understood in the artists' own times. Some of the texts in this treasury fall into the broad category of aesthetic theory; some describe specific techniques; some discuss the work of individual artists. The texts are presented in accurate and readable translations, and prefaced with artistic and historical background information to the formative periods of Chinese theory and criticism. A glossary of terms and an appendix containing brief biographies of 270 artists and critics add to the usefulness of this volume."--JSTOR website (viewed May 30, 2017).